2015
DOI: 10.3103/s1063457615040048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the contact conductivity of the diamond–metal binder interface on the thermal conductivity of diamond-containing composites

Abstract: The effect has been studied of the contact conductivity of the diamond-metal binder interface on the thermal conductivity of diamond containing composites having two and three component nickel based metal binders. A device and procedure have been developed for measuring the thermal conductivity coefficients of binders and based on them diamond containing composites. The dependence of the ther mal conductivity coefficients on the compositions (particularly, the presence of the carbide forming addi tives) and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The obtained thermal conductance value in [34]. This value is approximately 5% of the theoretical thermal conductance between nickel and diamond.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 77%
See 2 more Smart Citations
“…The obtained thermal conductance value in [34]. This value is approximately 5% of the theoretical thermal conductance between nickel and diamond.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 77%
“…2a shows an SEM micrograph of the as-received diamond particles. As indicated by the manufacturer, the particle shapes are mostly cubo-octahedral with 8 hexagonal/triangular (111) sides and 6 quadrilateral (100) sides [34]. The size distribution as determined from SEM micrographs of the diamond particles is shown in fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition of chromium on the surface of diamond increases effective thermal conductivity of diamond composite with Ni + 6%Sn binder by 15 -25%, that is a probable consequence of interface chemical reactions. The obtained data were interpreted with aid of the micromechanical model of composite with imperfect interface [14] predicting the effective thermal conductivity of composite as well as evaluating the interface contact conductivity by solving the inverse problem. It has been found that adding Cr increases the contact thermal conductivity of diamond-binder interface tenfold, from 2.1·10 6 to 2.3·10 7 W/(m 2 •K) [14] being typical value for chemical bonding case [15].…”
Section: Dcm Characterizationmentioning
confidence: 99%
“…The obtained data were interpreted with aid of the micromechanical model of composite with imperfect interface [14] predicting the effective thermal conductivity of composite as well as evaluating the interface contact conductivity by solving the inverse problem. It has been found that adding Cr increases the contact thermal conductivity of diamond-binder interface tenfold, from 2.1·10 6 to 2.3·10 7 W/(m 2 •K) [14] being typical value for chemical bonding case [15]. [16], which consists in conducting a series of tests ( fig.…”
Section: Dcm Characterizationmentioning
confidence: 99%